Solitary fibrous tumor of the pleura – analysis of 18 cases - Cieślik-Wolski, Bartosz; Pryt, Łukasz; Szlachcińska, Aleksandra; Walczak-Pasz, Grażyna; Jesionek-Kupnicka, Dorota; Kozak, Józef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Solitary fibrous tumors of the pleura (SFTP) are primary tumors arising from mesenchymal cells. Immunohistochemical studies have demonstrated that the origin of these tumors is mesenchymal rather than mesothelial. The aim of this study is to present our experience with diagnosing and treating patients with SFTP. Material and methods : We analyzed 18 patients treated at the Department of Thoracic Surgery of the Medical University of Lodz. The patients’ medical histories and the results of postoperative histopathological investigation of the tumors were analyzed. Postoperative histopathological samples were evaluated with regard to the current criteria of malignancy. Results: In 17 patients, the tumors were surgically removed. Benign and small lesions (less than 3 cm in size) were removed by video-assisted thoracoscopic surgery (VATS). In 5 cases, malignant tumors were found in the postoperative material. Conclusions: Solitary fibrous tumors of the pleura is a tumor with frequently asymptomatic clinical course. Treatment consists in resection which includes the adjacent structures, especially if the tumor is malignant.